O planejamento regional e urbano e a questão ambiental: análise da relação entre o plano de bacia hidrográfica Tietê-Jacaré e os Planos Diretores Municipais de Araraquara e São Carlos, SP - Peres, Renata Bovo (2012)
This Thesis is included on the discussion about the integration of the environmental dimension in the territorial management. More specifically, discuss the manner how the environmental issues have been treated in the tools and practices of management located at two territorial limits: in the municipal planning and in the regional planning by river basin. Even there have been advances related on the environmental concern in the territorial policies, this is one of the major frontiers of confrontation between agents who act and transform spaces, presenting situations of conflicts. The implementation of an integrated environmental management and planning deals with one of these challenges, the build of interfaces and joints among the tools and levels of the environmental policy with the municipal and regional policies. In this context, the general goal of this work is to analyze the relation between the environmental dimension and the municipal and regional planning, respectively, by the River Basin Plans and the Master Plans, specifically the Unit of Water Resources Management Tietê‐Jacaré from São Paulo State (UGRHI‐13). As research objects, were selected the River Basin Tietê‐Jacaré Plan and the Master Plans of Araraquara and São Carlos, both municipalities located at this territory. The research is exploratory, descriptive and analytic, considering the following categories of analyzes: definition of the local and regional units of management and planning; environmental tools in the river basin plan and in the urban plans; forums of local and regional management and planning; influence degree among the analyzed tools. Bibliographic and documentary revision and analyses, semi‐structured interviews and questionnaires were done. The regional planning by river basin presents a great potential about the integration aspects between the natural and human systems, from the proper use and occupation of territory, taking in account the social and environmental conditions. The River Basin Plan is a reference tool to guide the water use and land use in the respective region, although there are still gaps and difficulties in a more effective and expanded implementation. In the actual manner, it is considered as a tool extremely technical which has being poorly used in the management forums. It has being used more as a diagnosis of the environmental condition of the river basin than as a really inducer tool for policies. It doesn´t recognize the conflicts of land use and territorial organization as a vulnerability which needs to be addressed. The town planning is the principal conductive agent to the land use, mainly urban. In terms of territorial policies, the decisions are made at municipal levels. The master plans present opportunities to guide public policies which have been built from social forces, although still concentrate on the application of tools to urban zoning. The environmental conditions and aspects are presented as a margin thematic and weakly articulated with other policies. In the same way, there is a lack of regional aspects in the master plans, in order to understand that the environmental discussion presents an extension beyond the municipal limits. In the master plans appear few references to other forums and tools of regional planning, as the River Basin Plans and Committees. Therefore, the analysis of this work tried to demonstrate the complex relation among the policies, tools and forums of municipal and regional management and planning, showing the technical, political‐institutional and legal barriers which hinder the application of the Integrated Territorial Management concept.